2009
DOI: 10.4103/0972-0707.53335
|View full text |Cite
|
Sign up to set email alerts
|

International Caries Detection and Assessment System: A new paradigm in detection of dental caries

Abstract: A new emphasis on caries measurement and management is required for the dental community. The dental professionals need new approaches in caries detection, its assessment, and management. The future of research, practice, and education in Cariology requires the development of an integrated definition of dental caries, and uniform systems for measuring the caries process. Keeping this in view, the International Caries Detection and Assessment System (ICDAS) has presented a new paradigm for the measurement of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 9 publications
(7 reference statements)
1
66
0
6
Order By: Relevance
“…This is an important observation given that the principles applied to the criteria for primary caries are also applied to CARS. 11 However, it should be noted that the scientific basis for that has not been established and the literature in the area is limited. It should be also stressed that there is difficulty directly inspecting the approximal surfaces once the adjacent tooth and gingival tissue hamper visual access, especially when a restoration is involved, complicating the differentiation between noncarious changes and secondary caries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is an important observation given that the principles applied to the criteria for primary caries are also applied to CARS. 11 However, it should be noted that the scientific basis for that has not been established and the literature in the area is limited. It should be also stressed that there is difficulty directly inspecting the approximal surfaces once the adjacent tooth and gingival tissue hamper visual access, especially when a restoration is involved, complicating the differentiation between noncarious changes and secondary caries.…”
Section: Discussionmentioning
confidence: 98%
“…10 Given that outer lesions from secondary caries are considered similar to primary caries, the broad principles applied to the criteria for primary caries can also be applied to caries around restorations and sealants (CARS). 11 Research has shown that the ICDAS presents good reproducibility and accuracy for in vitro and in vivo detection of primary caries lesions at different stages of the disease. 10,[12][13][14][15] To our knowledge, no studies have been published that evaluate the performance of the ICDAS visual criteria in the detection of caries around restorations on approximal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The most common intraoral risk factor for root caries in adults is increased gingival recession leading to exposed roots. 17 From clinical findings it can be assumed that an individual with a high risk of coronal caries has a higher chance of developing root caries, indicating that risk factors for both type of caries are more or less the same.…”
Section: Risk Factors For Root Cariesmentioning
confidence: 99%
“…17 Most studies have shown that the majority of root caries are primary lesions. This indicates that controlling/modifying risk factors can prevent caries.…”
Section: Risk Factors For Root Cariesmentioning
confidence: 99%
“…1 a, b Radiographic appearance of typical carious lesions accepted into the study and informed consent was obtained (from a guardian, with pediatric patients). To be included in the study, patients had to have been diagnosed with clinically and radiographically significant carious lesions according to ICDAS (code 4-5) [19], which extended 0.5-1.5 mm into dentin (Figs. 1 and 2).…”
Section: Patient Selectionmentioning
confidence: 99%